Existence and stability of collinear points in elliptic restricted three body problem with radiating and oblate primaries - Chakraborty, Anindita; Narayan, Ashutosh; Shrivastav, Amit (International Journal of Advanced Astronomy, 2016)
The location of the collinear points in elliptical restricted three body problem, taking into account the effect of oblateness and radiation pressure of both primaries, has been obtained in this paper. Vinti's method has been exploited and the x-coordinates are obtained in the form of series solution. The linear stability has been investigated and it is found that the points are unstable in the Lyapunov's sense. The problem is also numerically explored taking into account two binary systems: Luyten-726 and Kruger-60.